ECTOPIC PREGNANCY: THE ROLE OF ULTRASOUND IN EARLY DIAGNOSIS OF LOWER ABDOMINAL PAIN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Ectopic pregnancy is a potentially life-threatening condition in which a fertilized egg implants outside the uterine cavity, commonly in the fallopian tube. Early diagnosis is crucial to prevent complications such as tubal rupture and hemorrhage. Ultrasound has emerged as a vital imaging tool for early identification of ectopic pregnancies, particularly in patients presenting with lower abdominal pain. This study explores the diagnostic value of ultrasound in detecting ectopic pregnancies and discusses its impact on clinical outcomes. Findings highlight the critical role of ultrasound, emphasizing the need for timely scanning to improve maternal safety.